Pengembangan Media Pembelajaran berbasis Instagram pada Sub Bahasan Fungsi Sepotong–Sepotong untuk Siswa SMA - Lanti Zita Nuryani; I Nyoman Arcana; Irham Taufiq (Jurnal Ilmiah Profesi Guru (JIPG), 2021)
The purpose of the study was to (1) develop instructional media using Instagram in mathematics subjects piecemeal material for high school students. (2) knowing the feasibility of the learning media. The type of research used is Research and Development (R&D) with a research model from ADDIE consisting of 5 stages, namely: Analysis, Design, Development, Implementation, and Evaluation. The subjects of this study were 36 students of class X IPA2 of SMA Negeri 1 Minggir. Data collection techniques using expert validation questionnaires, student response questionnaires, and learning achievement tests. The data analysis technique is descriptive qualitative. Based on the results of the validation, the Instagram learning media created were declared suitable for use and included in the valid category with an average of 4.04. From the results of the students' responses, it was found that the instagram learning media was suitable for use in learning and included in the valid category with an average of 3.43 Assessment of student learning outcomes shows that the number of students who meet the KKM is 16 students or 44.44%. This shows that the learning media developed are effectively used in learning. Instagram media is able to pierce photos and videos that can be accessed by anyone easily, quickly, wherever and whenever, it is expected that Instagram learning media is able to provide an understanding of the material in piecemeal functions and foster student interest in learning.